(untitled) (Journal of Applied Business and Economics, 2022)
This study examined how enterprise growth factors affect the return on venture capital investment for enterprises listed on Chinese Growth Enterprise Market (GEM). Using a sample of 235 venture capital backed enterprises listed on Chinese GEM over three years, we collected data from each company’s prospectus and listing documents. We also collected data from Chinese QINGKE Research Center Database. We found that (1) three growth factors (profitability, operational capability and innovation capability) were positively associated with venture capital return. (2) Both the composite growth indicator and the optimized composite growth indicator are positively related to venture capital return. The theoretical and practical implications are discussed.